EFEKTIVITAS MEDIA PEMBELAJARAN MULTIMODAL DALAM MENINGKATKAN KETERAMPILAN MEMBACA KRITIS SISWA SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Nur Khoiriyah, Anazwa; Dwi Puspitasari, Wina; Suhandi Saputra, Dudu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of technology in education has encouraged the development of multimodal learning media that combines various forms of representation, such as text, images, audio, and interactive elements. This type of media has the potential to support elementary school reading instruction by providing more engaging and meaningful learning experiences. This study aims to analyze the use of multimodal learning media in elementary school reading instruction, including the types of media developed and their impacts on students’ reading abilities. This study employed a Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The data were obtained from fifteen scientific articles published in national and international journals between 2020 and 2026. The selected articles were analyzed based on research characteristics, media types, research methods, and main findings. The results indicate that the most commonly used multimodal learning media include interactive e-books, digital storytelling, interactive multimedia, digital storybooks, digital picture books, and digital audio storybooks. The implementation of these media positively contributes to students’ reading literacy, reading comprehension, learning motivation, engagement, and critical thinking skills. However, studies specifically focusing on the development of multimodal media to improve critical reading skills remain limited. Therefore, the development of story-based multimodal media provides an opportunity to support more interactive reading instruction and foster higher-order thinking skills among elementary school students.